Pollen morphology of Verbascum L. (Scrophulariaceae) in Northern and Central Iraq (Bangladesh Journal of Plant Taxonomy, 2014)
The present study highlights the taxonomic values of the pollen features of 20 species of Verbascum L. in Iraq. The pollen grains were acetolysed and observed under Light and Electron microscopes. Our results showed that the pollen grains of these species are usually radially symmetrical, isopolar, tricolporate and display reticulate sculpturing. The variations were found in shape, size, and exine thickness. Most of the species are subprolate, prolate spheroidal, and prolate, whereas oblate spheroidal pollens were found only in V. thapsus. The pollen size among the species studied ranges from 16.2-32.5 µm. The majority of species are medium sized except V. agrimoniifolium and V. oreophilum that are small sized, and four species i.e. V. palmyrense, V. sinuatum, V. songaricum, and V. thapsus having both small and medium sized pollen grains. Moreover, the result showed that the exine thickness ranges from 0.87-4.75 µm, but this value can overlap between some species. Therefore, only the shape of pollen grains could be used to classify these species into groups.DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21355Bangladesh J. Plant Taxon. 21(2): 159-165, 2014 (December)